2005
DOI: 10.1021/ic050190k
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Borates:  Two New Polymorphs of BiB3O6

Abstract: Two new polymorphs of BiB3O6 were identified at low temperatures using boric acid as a flux. Unlike alpha-BiB3O6, which crystallizes in a noncentrosymmetric space group and, thus, shows exceptional nonlinear optical (NLO) properties, beta-BiB3O6 (I) and gamma-BiB3O6 (II) crystallize in the centrosymmetric space group P2(1)/n with the following lattice parameters: a = 14.1664(1), b = 6.7514(1), c = 4.4290(1) angstroms, beta = 102.125(1) degrees for I; and a = 8.4992(1), b = 11.7093(1), c = 4.2596(1) angstroms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…3). Due to the fact that the crystal structure of d-Ce(BO 2 ) 3 is isotypic to g-BiB 3 O 6 [33], the latter shows the same similarities and differences to the new Ce 2 B 8 O 15 as mentioned before.…”
Section: Crystal Structuresupporting
confidence: 60%
“…3). Due to the fact that the crystal structure of d-Ce(BO 2 ) 3 is isotypic to g-BiB 3 O 6 [33], the latter shows the same similarities and differences to the new Ce 2 B 8 O 15 as mentioned before.…”
Section: Crystal Structuresupporting
confidence: 60%
“…These include at least five stable crystalline phases: Bi 24 B 12 O 39 (boron sillenite) [8,9], Bi 4 B 2 O 9 [8,10], Bi 3 B 5 O 12 [8,11], BiB 3 O 6 (bismuth triborate) [5,8,[12][13][14], Bi 2 B 8 O 15 (bismuth octaborate) [8,[15][16][17] and one metastable phase (that was missing in original phase diagram given in reference [8]): BiBO 3 (bismuth orthoborate), and its two polymorphs (BiBO 3 -I and BiBO 3 -II) [18][19][20]. A number of earlier studies have reported the density, thermal, optical and structural studies of Bi 2 O 3 -B 2 O 3 glasses [1,[21][22][23][24][25][26] and melts [27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, six different polymorphs are known for BiB 3 O 6 [8][9][10][11][12]. The α-, β-and γ-BiB 3 O 6 could be obtained at ambient pressure [8].…”
Section: Introductionmentioning
confidence: 99%